Cell Condensation Triggers the Differentiation of Osteoblast Precursor Cells to Osteocyte-Like Cells - Jeonghyun Kim; Taiji Adachi (Frontiers in Bioengineering and Biotechnology, 2019)
Though the three-dimensional (3D) in vitro culture system has received attention as a powerful tool for conducting biological research, in vitro bone formation and osteocyte differentiation studies have mostly been based on results obtained using two-dimensional (2D) culture systems. Here, we introduced a rotatory culture system to fabricate 3D spheroids, using mouse osteoblast precursor cells. These spheroids, incubated for 2 days without chemical induction by osteogenic supplements, exhibited notably up-regulated osteocyte marker levels; osteoblast marker levels were down-regulated, as compared to those of the conventional 2D monolayer model. The cell condensation achieved with the 3D spheroid structure triggered a greater level of differentiation of osteoblast precursor cells into osteocyte-like cells than that observed during chemical induction. Our study might imply that osteoblasts proliferate and become condensed at the targeted bone remodeling site, because of which osteoblasts achieved the capability to differentiate into osteocytes in vivo.